INVERSI 1-D DATA MAGNETOTELLURIK YANG BEBAS DISTORSI - Hutahean, Juniar
Abstract: It is important to determining an estimation with high precision of the conductivities disribution of materials beneath the earth\'s surface 1 I) for correct interpretation of the magnetotelluric (MT) sounding. Intact, the earth\'s electrical conductivity is usually not simply depth dependent, where lateral conductivity changes that can cause distortion in the MT response curves. To solve this problem, an algorithm was developed which transforming the su: ;ace impedance response into a nondimensional complex logarithm response which invariant of distortion, and the misfit of the model respon to the observed logarithm response are seen to be invariant with respect to the distortion. From the algorithm, computing the partial derivatives _ response logarithm, and iteratively solving by damped least squares for conductivities contrast between layers. Smoothing is carried out to minimize the error. Beside ability to avoid difficulty in determining of initial model values, this inversion algorithm test with synthetic data shows that this algorithm is efficient and accurate.